A Capital Budgeting Analysis of Life Insurance Costs in the United States: 1950-1979 - Babbel, David F.; Staking, Kim B. (Journal of Finance, 1983)
A capital budgeting procedure is applied in developing a real price index for life insurance over three decades. Individual life policies of three types are analyzed. The analysis reveals that although the cost of whole life insurance, measured in nominal values, has decreased over the past thirty years, when properly measured in present value or constant dollar terms, the cost has risen substantially. Term life insurance has been characterized by decreasing costs in both nominal and real terms. The amounts of the cost variations attributable to improving survival rates, changing policy terms, varying discount rates and differing tax status are identified.